2012
DOI: 10.5483/bmbrep.2012.45.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity and hypolipidemic effects of Rheum undulatum in high-fat diet-fed C57BL/6 mice through protein tyrosine phosphatase 1B inhibition

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is important in the regulation of metabolic diseases and has emerged as a promising signaling target. Previously, we reported the PTP1B inhibitory activity of Rheum undulatum (RU). In the present study, we investigated the metabolic regulatory effects of RU in a high-fat diet (HFD) model. RU treatment significantly blocked body weight gain, which was accompanied by a reduction of feed efficiency. In addition, it led to a reduction of liver weight mediated by overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Under severe insulin resistance, insulin secretion is significantly reduced and results in serious hyperglycemia. Chrysophanol, physcion and emodin showed moderated bioactivity against human protein tyrosine phosphatase in vitro [141], and they strongly enhanced insulin sensitivity [142]. Quercetin prevented the TNF alpha-mediated phosphorylation of insulin receptor substrate 1, protein tyrosine phosphatase kappa B gene expression and the suppression of insulin stimulated glucose uptake [139].…”
Section: Resultsmentioning
confidence: 99%
“…Under severe insulin resistance, insulin secretion is significantly reduced and results in serious hyperglycemia. Chrysophanol, physcion and emodin showed moderated bioactivity against human protein tyrosine phosphatase in vitro [141], and they strongly enhanced insulin sensitivity [142]. Quercetin prevented the TNF alpha-mediated phosphorylation of insulin receptor substrate 1, protein tyrosine phosphatase kappa B gene expression and the suppression of insulin stimulated glucose uptake [139].…”
Section: Resultsmentioning
confidence: 99%
“…Chrysophanol increased glucose transport activity and elevated the tyrosine phosphorylation of insulin receptor via inhibiting tyrosine phosphatase 1B (PTP1B) activity and increasing the expression of Glut4 mRNA in L6 rat myoblasts . In‐vivo research showed that the combination of chrysophanol and emodin could inhibit PTP1B activity and strongly enhanced insulin sensitivity of HFD (high‐fat diet)‐fed mice . Subsequent research showed that chrysophanol was a competitive PTP1B inhibitor .…”
Section: Pharmacologymentioning
confidence: 99%
“…Chrysophanol isolated from S. obtusifolia and rhubarb rhizome inhibited PTP 1B activity (IC 50 : 5.8 μM) and stimulated glucose transport in insulin‐stimulated myotubes (Babu et al, ; Jung et al, ; Lee & Sohn, ; Lee, Yoon, Hwang, Kim, & Kim, ). Chrysophanol glucosides, chrysophanol‐8‐O‐β‐D‐glucopyranoside, chrysophanol triglucoside, and chrysophanol tetraglucoside from S. obtusifolia inhibited PTP 1B activity with IC 50 values of 8.8, 80.17, and 103.89 μM, respectively (Jung et al, ).…”
Section: Resultsmentioning
confidence: 99%